2023
DOI: 10.1021/acs.organomet.3c00299
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Synthesis and Applications of N-Heterocyclic Carbene Metal Complexes with a Focus on the Weak Base Route

Thomas Scattolin,
Aleksei A. Logvinov,
Nikolaos V. Tzouras
et al.

Abstract: N-heterocyclic carbene (NHC) ligands have evolved from being simple lab curiosities to tertiary phosphine mimics to finally take center stage as unique supporting ligands in organometallic chemistry, homogeneous catalysis, and more recently in medicinal chemistry and materials science applications. Some of these aspects are presented here from a perspective of researchers that have been fascinated by the area for quite some time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 214 publications
(244 reference statements)
0
4
0
Order By: Relevance
“…N -heterocyclic carbene (NHC) ligands have emerged as pivotal components in modern organometallic chemistry, revolutionizing catalytic processes and enhancing the versatility of transition metal complexes. Since their discovery in the 1980s, NHC ligands have garnered significant attention owing to their unique electronic and steric properties, which make them ideal candidates for a wide range of applications [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…N -heterocyclic carbene (NHC) ligands have emerged as pivotal components in modern organometallic chemistry, revolutionizing catalytic processes and enhancing the versatility of transition metal complexes. Since their discovery in the 1980s, NHC ligands have garnered significant attention owing to their unique electronic and steric properties, which make them ideal candidates for a wide range of applications [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…2-methyl-6-((phenylthio)methyl)pyridine, Pt(dba) 2 ( E )-1,2-ditosylethene and silver-NHC complexes 5a , b were synthetized according to the published procedures [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…24,27 The latter are usually considered as an attractive alternative to tertiary phosphines, owing to their ability to form strong bonds with transition metals. 28…”
Section: Introductionmentioning
confidence: 99%
“…5 Most investigations carried out so far focused on the synthesis of transition metal complexes bearing NHC ligands via a concerted metalation/deprotonation path. 6 Yet, recent work from our Laboratory has shown that imidazol(in)ium salts could easily perform a nucleophilic addition on CS 2 in the presence of Cs 2 CO 3 to afford zwitterionic dithiocarboxylate adducts (Scheme 1a). 7 Thus, we wanted to determine whether NHC·HX salts could also undergo a nucleophilic substitution under the same experimental conditions (Scheme 1b).…”
mentioning
confidence: 99%